2010
DOI: 10.1002/ibd.21097
|View full text |Cite
|
Sign up to set email alerts
|

TLR5 is not required for flagellin-mediated exacerbation of DSS colitis

Abstract: Together, these results suggest that flagellin-mediated exacerbation of colitis is independent of TLR5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…57 However, the exact role of TLR5-dependent signaling in colitis remains to be elucidated since it has been demonstrated that DSS-induced colitis is more severe in TLR5-deficient mice rectally treated with purified flagellin than in identically treated wild-type mice. 58 A more protective role of TLR5-dependent host responses toward gut bacteria may also be concluded from the fact that TLR5 -/-mice are prone to spontaneously developing transmural colitis. Interestingly, this phenotype was not observed in mice simultaneously deficient for TLR4 and TLR5 suggesting that TLR4 ligands trigger colitis in TLR5 -/-mice.…”
Section: Gram Negative Bacteria In Chronic Colitismentioning
confidence: 99%
“…57 However, the exact role of TLR5-dependent signaling in colitis remains to be elucidated since it has been demonstrated that DSS-induced colitis is more severe in TLR5-deficient mice rectally treated with purified flagellin than in identically treated wild-type mice. 58 A more protective role of TLR5-dependent host responses toward gut bacteria may also be concluded from the fact that TLR5 -/-mice are prone to spontaneously developing transmural colitis. Interestingly, this phenotype was not observed in mice simultaneously deficient for TLR4 and TLR5 suggesting that TLR4 ligands trigger colitis in TLR5 -/-mice.…”
Section: Gram Negative Bacteria In Chronic Colitismentioning
confidence: 99%
“…13 A protective effect of TLR5 on epithelial cells may also explain the susceptibility of 5À/À mice to DSS colitis. 6 In addition, there is growing evidence that expression of TLRs other than TLR5 on T cells may protect against colitis. For instance, deletion of TLR4 or 9 increases the colitogenic capacity of conventional CD4 þ T cells, suggesting that TLR signaling may inhibit pathogenic T cell responses.…”
mentioning
confidence: 99%
“…5 The role of TLR5 signaling in IBD is also evident from studies in murine IBD models. TLR5-deficient (5À/À) mice show increased sensitivity to dextran sulfate sodium (DSS)-induced colitis, which causes epithelial damage, 6 and develop spontaneous colitis in some animal facilities. 7 The cell types that express TLR5 and regulate mucosal immunity via a TLR5-dependent mechanism, however, remain unclear.…”
mentioning
confidence: 99%
“…For example, deficiency in TLR2, TLR4, TLR5, and TLR9 has been individually associated with the increased susceptibility to DSSinduced colitis Ivison et al, 2010;Lee et al, 2006;Rakoff-Nahoum et al, 2004). Mice deficient in MyD88, a major downstream molecule of most TLRs except for TLR3, also demonstrated more severe disease than WT mice in this colitis model suggesting the importance of MyD88-dependent TLR signaling in protection against chemically induced mucosal damage Rakoff-Nahoum et al, 2004).…”
Section: Role Of Prrs In Acute Murine Colitismentioning
confidence: 88%
“…By contrast, rectal administration of flagellin has been reported to aggravate DSS-induced colitis (Rhee et al, 2005). The discrepancy of the flagellin effect may be due to administration route (systemic vs. topical), but a recent report has suggested that flagellin-mediated aggravation of colitis is independent of TLR5 signaling as the exacerbation of DSS colitis by flagellin is also observed in TLR5-deficient mice (Ivison et al, 2010). TLR5 agonist has been under preclinical stage, but further screening of its efficacy and adverse effects using different mouse models of colitis may be required in addition to clarifying the effector component of flagellin and optimization of their administration route.…”
Section: Tlr5mentioning
confidence: 99%